Reclaiming the hunting ground: an examination of college students' receptiveness towards sexual violence prevention programming and education - Knight, Trina Kristine (My University, 2026)
Each year, millions flock to colleges and universities to revel in nearly limitless opportunities for personal and professional development, scholastic discovery, and social connection. Approximately 13% of college students will experience sexual violence during their matriculation, and of these experiences, an estimated 90% will go unreported. Scholars continue to explore and examine the persistence of this phenomenon despite institutional and federal interventions which ensure the provision of prevention and response programs and services on college campuses. While studies examining sexual violence prevention have contributed knowledge regarding best practices in prevention programming, risk factors, and program evaluation, there is a dearth of literature that examines how sexual violence prevention programming and education is received by students. The primary purpose of this study was to identify which factors most influence college students’ receptiveness to sexual violence prevention programming and education. Survey data for this study were collected from a sample of 614 undergraduate college students from a mid-sized Midwestern university. A quantitative examination of these data indicated that college students who reported greater levels of perceived campus safety and empathy as well as those who identified as women or nonbinary and as upperclassmen demonstrated higher levels of receptiveness towards sexual violence prevention programming and education. The theoretical and practical implications of these findings are considered in the final chapters of this dissertation.
Keywords: Sexual violence; Sexual violence prevention; Rape myth acceptance; Empathy; Victim-blaming; Institutional betrayal; Campus safety